Correlation between Fast Food Eating Habits and the Occurrence of Dysmenorrhea - Herdiani, Ida; Ediyono, Suryo (INDOGENIUS, 2025)
Background : Dysmenorrhea is a common complaint experienced by women of reproductive age, including female students, characterized by pain in the lower abdomen during menstruation. One factor that is thought to contribute to dysmenorrhea is dietary habits, particularly the consumption of fast food that is high in saturated fat and sodium. Objective: This study aims to determine the correlation between fast food consumption habits and the incidence of dysmenorrhea in female students aged 18–25 years. Methode: This study used a descriptive analytical design with a cross-sectional approach. A total of 140 female students were selected as respondents using accidental sampling. Data were collected through questionnaires and analyzed using the chi-square test. Results: The results showed that 135 female students (96.4%) experienced dysmenorrhea, and 137 female students (97.9%) had a habit of frequently consuming fast food.   The chi-square test results showed a significant relationship between fast food consumption and the incidence of dysmenorrhea (p = 0.0).  Conclusion: It can be concluded that the habit of eating fast food is associated with the incidence of dysmenorrhea in female students. Education about healthy eating patterns is important as an effort to prevent dysmenorrhea.